PENGARUH KESADARAN WAJIB PAJAK, PENGETAHUAN PAJAK, SIKAP WAJIB PAJAK DAN REFORMASI ADMINISTRASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Winda Kemala; Kennedy -; Rusli - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This studyaimed toanalyze the effect caused by the variable tax payer awareness, knowledge of tax, attitude tax payer and reform of tax administration with motor vehicletax compliance. This study uses accidental sampling with 100 samples obtained from the calculation formula slovin. Data collection techniques in this study is in the form of questionnaires, while data analysis technique used is multiple regression analysis were processed with SPSS version 17 for Windows. From the results of the testing that has been done, simultaneous regression test (F test) showed that all independent variables studied have a simultaneous effect on the variable motor vehicle tax compliance. Partial regression test (t test) showed that all independent variables studied partial effect on the variable motor vehicle tax compliance. The magnitude of the effect caused by Adjusted R2by four variables together against the dependent variable 57.7%, while the remaining 42.3% is influenced by other variables not examined in this study.Keywords: awarenesstaxpayer, knowledge of tax, attitude taxpayer, reform of tax administration, tax compliance.